2004
DOI: 10.1108/09555340410565404
|View full text |Cite
|
Sign up to set email alerts
|

Web site accessibility of German and UK tourism information sites

Abstract: Information exchange is important in any transaction but is perhaps particularly important for transactions in the travel and tourism industry where information gratification plays such a crucial role. Internet‐based technologies allow organisations to exchange information with an often geographically dispersed and wider marketplace without a loss of quality. However, merely being online, publishing a Web site is not enough. Organisations need to ensure their Web sites obtain “traffic” or “hits” and, important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…More specifically, while the majority of the websites under examination (17) include sufficient information regarding accessibility for travellers with special needs, only 2 of them (the Spanish and the British NTO) declare that their portals are adhering with the legal imperatives for accessibility according to the web content accessibility guidelines (http// w3.org). This is consistent with the findings of Williams et al (2004) who found discouraging low levels of accessibility for tourism related websites in Germany and UK. A further category where the sample portals are performing particularly weakly is service integration, averaging 12 % across the total sample.…”
Section: Customer Perspective Findingssupporting
confidence: 92%
“…More specifically, while the majority of the websites under examination (17) include sufficient information regarding accessibility for travellers with special needs, only 2 of them (the Spanish and the British NTO) declare that their portals are adhering with the legal imperatives for accessibility according to the web content accessibility guidelines (http// w3.org). This is consistent with the findings of Williams et al (2004) who found discouraging low levels of accessibility for tourism related websites in Germany and UK. A further category where the sample portals are performing particularly weakly is service integration, averaging 12 % across the total sample.…”
Section: Customer Perspective Findingssupporting
confidence: 92%
“…• city accessibility pedestrianisation and wayfinding principles create more accessible and environments (Aslaksen et al, 1997;Gleeson, 2001;Goldsmith & PRP Architects, 2000;and Hall & Imrie, 2001;Imrie, 1996;Sawyer & Bright, 2004) • disability studies and the geographies of disability where the role of space and place is interrogated from a disability perspective (Abberley, 1987;Oliver, 1990Oliver, , 1996Chouinard, 1997;Chouinard & Grant, 1995;Cormode, 1997;Crouch, 2000;Golledge, 1996;Hahn, 1986;Imrie, 1996Imrie, , 2000Kitchin, 1998Kitchin, , 2000aWilton, 1999) • historic building accessibility, where dynamic reuse has been championed by architects and planners who regard heritage as an evolving consideration over time ( • information provision and website design, where alternative format provision and W3C international protocols for website accessibility place the responsibility for such provision with organisations (Cameron, Darcy, & Foggin, 2003;Human Rights and Equal Opportunity Commission, 2002;Shi, 2006;Williams, 2004).…”
Section: Figurementioning
confidence: 98%
“…Given that "security is not free, and in fact, on the web, it is particularly expensive" (p. 99) (Stubblefield, Rubin & Wallach, 2005), other means of reinforcing security perceptions should be activated, for example, building highly usable pages. Benefits of usability are good for everyone (Williams, Rattray & Stork, 2004). So, firms have to communicate effectively with the target audience allowing them access to content.…”
Section: Theoretical Framework the Importance Of Website Securitymentioning
confidence: 99%